Zika Virus IgM 25 Months after Symptom Onset, Miami-Dade County, Florida, USA - Griffin, Isabel (Emerg Infect Dis, 2019)
We assessed IgM detection in Zika patients from the 2016 outbreak in Miami-Dade County, Florida, USA. Of those with positive or equivocal IgM after 12–19 months, 87% (26/30) had IgM 6 months later. In a survival analysis, ≈76% had IgM at 25 months. Zika virus IgM persists for years, complicating serologic diagnosis.